VIEWING VIDEOS ON THE NATIONAL GEOGRAPHIC CHANNEL TO IMPROVE STUDENTS' SPEECH SKILLS - Hasrida Ardin; Ary Irjayanti Herman (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2024)
The purpose of this study was to improve the speaking abilities of SMA Negeri 2 Baubau students in the eleventh grade by having them view videos using the national geographic channel approach. Eighty SMA Negeri 2 Baubau eleventh graders made up the sample. A test and questionnaire were used as the research instrument. One technique descriptive analysis was employed to analyze the data about the speaking achievement of the students at SMA Negeri 2 Baubau. Students' scores in both the control and experimental classes were described using a descriptive quantitative analysis. The results showed that students' speaking achievement at SMA Negeri 2 Baubau may be impacted by watching videos on the national geography channel. This discrepancy was evident in the t-test result of 8,291, which was higher than the t-table result of 2,021, indicating that the eleventh-grade students at SMA Negeri 2 Baubau are drawn to national geographic channel method videos.